The Relationship between Total Quality Management and Teacher Quality: Transformational Leadership as Mediator - Rahman, Mohd Rahimi A; Nor, Mohamed Yusoff Mohd; Wahab, Jamalul Lail Abdul; Mansor, Azlin Norhaini; Suliman, Ashairi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the relationship between total quality management practice and teacher quality in secondary schools besides to identify the effect of transformational leadership style on the relationship between both. This study used cross-sectional survey engaging 423 secondary school teachers from all over Malaysia. This study utilised Pearson's correlation inference analysis to determine the relationship between variables and SPSS Macro Process 3.0 analysis to identify the intermediate effect. The results showed that the relationship between total quality management practice and transformational leadership style, the relationship between transformational leadership style and teacher quality and the relationship between quality management practices and teacher quality are positive and significant. Additionally, the Variance Adjustment Factor (VAF) for mediator variable was 24.4%. Thus, this study has demonstrated that there is an intermediate effect between total quality management practice and teacher quality.